Quantum Simulation Study of Ultrascaled Label-Free DNA Sensors Based on Sub-10 nm Dielectric-Modulated TMD FETs: Sensitivity Enhancement Through Downscaling - Khalil Tamersit; Abdellah Kouzou; José Rodriguez; Mohamed Abdelrahem (Micromachines, 2025)
In this article, the role of downscaling in boosting the sensitivity of a novel label-free DNA sensor based on sub-10 nm dielectric-modulated transition metal dichalcogenide field-effect transistors (DM-TMD FET) is presented through a quantum simulation approach. The computational method is based on self-consistently solving the quantum transport equation coupled with electrostatics under ballistic transport conditions. The concept of dielectric modulation was employed as a label-free biosensing mechanism for detecting neutral DNA molecules. The computational investigation is exhaustive, encompassing the band profile, charge density, current spectrum, local density of states, drain current, threshold voltage behavior, sensitivity, and subthreshold swing. Four TMD materials were considered as the channel material, namely, MoS2, MoSe2, MoTe2, and WS2. The investigation of the scaling capability of the proposed label-free gate-all-around DM-TMDFET-based biosensor showed that gate downscaling is a valuable approach not only for producing small biosensors but also for obtaining high biosensing performance. Furthermore, we found that reducing the device size from 12 nm to 9 nm yields only a moderate improvement in sensitivity, whereas a more aggressive downscaling to 6 nm leads to a significant enhancement in sensitivity, primarily due to pronounced short-channel effects. The obtained results have significant technological implications, showing that miniaturization enhances the sensitivity of the proposed nanobiosensor.